Exploring Relationships with Non-human Nature in Planning: The Potential of Embodied Research Methodologies - Scherini, Rebecca (Curtin University, 2014)
The institutionalised land use planning system plays an important role in mediating our relationships with non-human nature. However, the dominant environmental discourses perpetuate a dualistic understanding of culture/nature, privileging scientific rationality over other ways of knowing, and humans over nature. Embodied research methodologies offer an alternative mode of knowledge production to those traditionally used within the system, allowing planning researchers a deeper and more nuanced understanding of the complexity of human relationships with non-human nature. In this paper I use examples from my honours thesis and PhD research to demonstrate the potential of embodied research methodologies for promoting more connected relationships to non-human nature.